2016
DOI: 10.1128/mcb.00641-15
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Upregulates the Constitutive and Virus-Induced Transcriptional Capacity of the Interferon Beta Promoter through T-Cell Factor Binding Sites

Abstract: . Rapid upregulation of IFN-␤ gene expression occurs after recognition of viral nucleic acids by pattern recognition receptors (PRRs) consisting of either cytosolic receptors, such as retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated antigen 5 (MDA-5), or membrane-associated Toll-like receptors, such as Toll-like receptor 3 (TLR3) (3). After sensing single-or doublestranded RNA of viral origin, these receptors activate signaling pathways, implicating the phosphorylation and nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 74 publications
(105 reference statements)
1
25
0
Order By: Relevance
“…We and others have observed that when this form accumulates in response to the use of GSK-3 inhibitors, in the presence of Wnt ligands, or through β-catenin overexpression, it negatively affects the type I IFN response in cells following RLR stimulation [88][89][90]. However, other groups have reported the opposite in response to RNA viruses, including influenza A virus, human immunodeficiency virus (HIV), bovine parainfluenza virus type 3, and Rift Valley fever virus [40,81,82,91,92].…”
Section: Cytosolic Rna Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have observed that when this form accumulates in response to the use of GSK-3 inhibitors, in the presence of Wnt ligands, or through β-catenin overexpression, it negatively affects the type I IFN response in cells following RLR stimulation [88][89][90]. However, other groups have reported the opposite in response to RNA viruses, including influenza A virus, human immunodeficiency virus (HIV), bovine parainfluenza virus type 3, and Rift Valley fever virus [40,81,82,91,92].…”
Section: Cytosolic Rna Sensorsmentioning
confidence: 99%
“…Due to the paucity of these studies, the working models have sometimes been in contradiction. However, pictures are emerging where (1) GSK-3 operates at the level of β-catenin [74] and/or TBK1 [75,76]; and (2) β-catenin acts via the classical holocomplex formed by IRF3 and CBP/p300 [74,[77][78][79][80][81] or TCF [82] to regulate the production of type I IFNs (Figure 3). receptor-associated factors (TRAFs) to polymerized MAVS results in the activation of the constitutively expressed protein kinase TANK-binding kinase 1 (TBK1) and its inducible homologue IKKi (or IKKε).…”
Section: Cytosolic Rna Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from Marcato et al[82] suggests that the TCF/β-catenin complex is instrumental in mounting an effective antiviral response. They linked two observations, namely, that IFN-β is needed during the innate antiviral response and that murine models lacking IFN-β are susceptible to viral infections.…”
Section: Speculation and Questionsmentioning
confidence: 99%